The PRagmatic EValuation of evENTs And Benefits of Lipid‐lowering in oldEr adults (PREVENTABLE) trial: Study design and procedures for cognitive assessment and adjudication. (31st December 2021) - Sachs, Bonnie C.; Rapp, Stephen R.; Kistler, Christine E; Musi, Nicolas; Supiano, Mark A.; Pajewski, Nicholas M.; Callahan, Kathryn E.; Alexander, Karen P.; Shah, Raj C; Snyder, Heather M.; Carrillo, Maria C.; Espinoza, Sara; et al.
Abstract: Background: No existing therapies for Alzheimer's disease and related dementias fundamentally alter the trajectory of the disease. While observational data suggests statins may reduce cognitive and functional decline in older adults, randomized evidence is lacking. Method: The PRagmatic EValuation of evENTs And Benefits of Lipid‐lowering in oldEr adults (PREVENTABLE) trial is funded by the National Institute on Aging, National Heart, Lung, and Blood Institute, and supported by the Alzheimer's Association. The trial will test the primary hypothesis that randomization to atorvastatin 40 mg versus placebo results in superior survival free of incident dementia or persistent physical disability over 5 years. The development of mild cognitive impairment (MCI) is a secondary endpoint. The target sample size is 20, 000 participants ≥75 years without dementia recruited from 90 sites across the US from the National Patient‐Centered Clinical Research Network and the Veterans Affairs system. The trial will use a pragmatic, standardized telephone‐based cognitive battery, centrally administered annually, which includes a cognitive screener, the Telephone Interview for Cognitive Status‐modified (TICSm). Based on TICSm scoring, an extended phone cognitive battery will be performed that includes measures of attention/executive function, verbal memory, language, and mood. In addition, the Functional Activities Questionnaire will be administered to a trusted contact. A telephone assessment of physical and functional status will also be administered annually. Cognitive and functional data will be adjudicated by a panel of experts, blinded to treatment assignment, to determine the occurrence of MCI (and subtype) or probable dementia. Result: PREVENTABLE will utilize pragmatic data sources (electronic health records and administrative claims) to obtain relevant medical data; however, these mechanisms are unreliable at identifying incident dementia and MCI. The pandemic required modification of cognitive testing, embracing a purely telephonic approach at baseline, which will nonetheless permit cognitive adjudication of participants. Recruitment will be ongoing through April 2023 with results available in 2026. Conclusion: PREVENTABLE represents the largest randomized pragmatic trial examining cognitive outcomes associated with statin use in older adults. Launching during the pandemic required adaptation to remote assessment, which will facilitate progress towards efficient and novel methods for pragmatic clinical trials aimed at preventing dementia.